Effect of Biopore Infiltration Hole on Soil Nutrient Availability and Nutrient Content of Coffee Leaves (Coffea canephora) - Zahrotun Naylis Syarof; Soemarno Soemarno; Lenny Sri Nopriani (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Coffee is an important plantation commodity for the Indonesian economy. However, coffee production has decreased due to low soil fertility. One effort to increase soil fertility is by applying Biopore Infiltration Hole. This study aimed to examine the effect of biopore on nutrient availability in coffee leaves (Coffea canephora) and soil in Jatikerto Field, Malang. The experiment used a randomized block design with four treatments: control, 30 cm depth biopore, 30 cm biopore + compost, and 30 cm biopore + goat manure. Nutrient content on leaves and soil chemical properties (total N, available P, K-exchangeable) were measured. The results showed that the application of BIH 30 cm plus goat manure, was able to significantly increase the availability of N, P, K nutrients in coffee leaves and also soil total N, available P, K-exchangeable. Overall, the application of BIH was able to increase soil fertility and nutrient uptake by coffee plants. Keywords: Biopore, Compost, Nutrients. Organic,